A Numerical Study on the Effectiveness of U-Shaped Steel Metallic Dampers Applied to Braced Building Structures under Dynamic Loading - Efrizal; Eka Satria; Irsal Oktofirnof; M. Raffi Akbar; Lovely Son; Dendi Adi Saputra; Mulyadi Bur (Department of Mechanical Engineering, Universitas Andalas, 2026)
The increasing demand for seismic-resilient structures has encouraged the development of advanced energy dissipation devices capable of reducing structural damage under strong ground motions. Among various passive control systems, metallic dampers have gained significant attention due to their stable hysteretic behavior, high energy dissipation capacity, and simplicity of installation. This study investigates the seismic performance of a building structure equipped with U-shaped steel metallic dampers installed within a chevron bracing system. The research is conducted through two complementary analytical stages. First, a detailed nonlinear finite element analysis is performed to evaluate the cyclic behavior of the U-shaped damper, accounting for both material and geometric nonlinearities. The resulting hysteresis curves are used to determine the elastic stiffness and energy dissipation capacity of the damper. In the second stage, the obtained mechanical properties are implemented into a dynamic numerical model of a multi-story building, where the damper is represented as spring element connecting the bracing system to the main structural frame. Linear time-history analyses are then conducted under earthquake ground motions to assess the dynamic response of the structure. The seismic performance of the damped structure is compared with that of an identical structure without metallic dampers in term of dynamic response. The results demonstrate that the proposed U-shaped metallic damper significantly enhances seismic performance by reducing structural demands and concentrating inelastic deformations within replaceable energy-dissipating components